2007
DOI: 10.1111/j.1745-3933.2007.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

The radius and mass of the subgiant star β Hyi from interferometry and asteroseismology

Abstract: We have used the Sydney University Stellar Interferometer to measure the angular diameter of β Hydri. This star is a nearby G2 subgiant the mean density of which was recently measured with high precision using asteroseismology. We determine the radius and effective temperature of the star to be 1.814 ± 0.017 R (0.9 per cent) and 5872 ± 44 K (0.7 per cent) respectively. By combining the radius with the mean density, as estimated from asteroseismology, we make a direct estimate of the stellar mass. We find a val… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 20 publications
0
40
1
1
Order By: Relevance
“…This has been done recently for a few nearby solar-like asteroseismic targets (see North et al 2007North et al , 2009) and yield T eff to about 50 K. Interferometric measurements of the relatively faint CoRoT targets (V 5−8) may be possible in the near future with the recently installed PAVO instrument at the CHARA array (Ireland et al 2008) or AMBER at VLTI (Petrov et al 2007). …”
Section: The Effective Temperaturementioning
confidence: 99%
“…This has been done recently for a few nearby solar-like asteroseismic targets (see North et al 2007North et al , 2009) and yield T eff to about 50 K. Interferometric measurements of the relatively faint CoRoT targets (V 5−8) may be possible in the near future with the recently installed PAVO instrument at the CHARA array (Ireland et al 2008) or AMBER at VLTI (Petrov et al 2007). …”
Section: The Effective Temperaturementioning
confidence: 99%
“…To compute the luminosity of β Hyi we used the same value for the bolometric flux as North et al (2007), F bol = (2.019 ± 0.05) × 10 9 W m −2 (Blackwell & Lynas-Gray 1998, the uncertainty on F bol is from di Benedetto 1998) and the revised Hipparcos parallax (van Leeuwen 2007). Adopting L = 3.842 × 10 26 W with an uncertainty of 0.4% (Bahcall et al 2001), we found L = 3.494 ± 0.087 L for β Hyi.…”
Section: Non-seismic Datamentioning
confidence: 99%
“…The radius was obtained by combining the interferometric angular diameter of the star, θ = 2.257 ± 0.019 mas (North et al 2007), with the revised Hipparcos parallax, π p = 134.07 ± 0.11 mas (van Leeuwen 2007).…”
Section: Non-seismic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2 that when these data are available, a direct estimation of the stellar mass and radius can be obtained (e.g., Silva Aguirre et al 2011;Stello et al 2008). These scaling relations seem to hold well for radius determinations (e.g., Huber et al 2012;North et al 2007;Silva Aguirre et al 2012;White et al 2013), while confirmation of masses is still under way using clusters and binaries. In order to determine ages for stars using the global seismic parameters, BASTA and BeSPP compare these quantities and the atmospheric parameters to those predicted by grids of models.…”
Section: The Bare Minimummentioning
confidence: 99%